NEW PROTOMEOTIAN BURIAL GROUND IN THE FOOTHILLS OF ADYGEA - Erlih, Vladimir Roal'dovic; Leont'eva, Anna Stanislavovna; Abramova, Aleksandra Nikolaevna (History, Archeology and Ethnography of the Caucasus, 2024)
This article presents materials from a newly discovered burial ground of the Protomeotian group of sites, located in the foothills of Adygea on the Azishsky Ridge near the village of Dakhovskaya. The burial ground was discovered by the team of the Caucasian Expedition LLC “Kulturnoye Nasledie” in 2023 (chief of the expedition – A.S. Leontieva) during the study of the mound “Azishsky-16,” the main burial of which dates to the Early Bronze Age. The Protomeotian burial ground was found overlaying this mound. The site contains nine burials with Proto-Meotian material, situated on a rocky base under a rock riprap, all in elongated positions with varying orientations. Except for one, all burials are of the single type. Grave goods primarily consist of adornments, including pins with oar-shaped and rounded heads, beads, a bracelet, spiral laces, and button plaques. A whetstone was found in one burial. Some burials, located on the Transcaucasian pass route, contain objects indicating connections with the Koban and Bzyb Colchian cultures. Notably, there are parallels in the grave goods and funeral rites with two burials from the Gagra burial ground (Abkhazia), dated to the 9th century BC. The absence of iron objects in these burials, along with the similarity of the burial material to the early group of the reference foothill burial Fars/Klady, suggests a tentative dating from the 9th to the first half of the 8th century BC. However, a key difference between the newly discovered site and the Fars/Klady burial ground is the lack of weapons and bridles in the male burials. Additionally, horse bones have not yet been found at this site.
Keywords: North Caucasus; Adygea; transition to the Iron Age; Protomeotian group of monuments; burial ground; decorations; Koban archaeological culture; Bzyb Colchis culture; connections; pass route.